Biases in the Literature on Direct Wildlife Mortality from Energy Development. (10th April 2019) - Loss, Scott R; Dorning, Monica A; Diffendorfer, Jay E
Abstract: Comparing environmental impacts of different energy sources can inform energy investments and environmental conservation. Direct wildlife mortality from energy development receives substantial public and scientific attention, but it is unclear whether rigorous comparisons of mortality among energy sources are possible. To address this question, we compared availability of mortality studies among energy sources, wildlife groups, and regions, and assessed comparability of mortality indicators measured. Whereas wind and hydropower have received substantial mortality research exceeding their proportional contributions to global energy production, coal, oil and gas, and bioenergy have received fewer studies and are underrepresented relative to their contributions. Furthermore, research is biased toward birds and fish and North America and Europe, and there are inconsistencies among energy sources and limited replication of most indicators measured. These results indicate that rigorous comparisons of direct wildlife mortality among energy sources are not currently possible and highlight research needs for improving understanding of energy's environmental impacts.